MANAGEMENT SERVICES AND THE CPA EXAMINATION. - Moss, Morton F. (The Accounting Review, 1962)
Abstract Management services have become an increasingly important part of the professional activities of the certified public accountants (CPA). The propriety of management services in public practice serve to reinforce those of the profession's leadership. Not only are management services in harmony with auditing, but there is a definite interrelationship between the two functions. Understandably, the development of standards and measurement of competence has lagged behind the growth of management services in public practice. At the present time the profession has left the matter of competence to the individual judgment of the CPA. But reliance on this tenuous standard is dangerous for a profession which is held in such high esteem by the public. To wear the mantle of CPA, and to measure competence successful passage of a comprehensive examination is required. It is recommended, therefore, that the scope of the examination be expanded to include either questions or problems or both relating to management services. The addition to the present examination of questions in the standard area of management services will aid materially in maintaining the prestige of the profession.